2013
DOI: 10.1073/pnas.1315587110
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic-mediated caspase activation is essential for cardiomyocyte hypertrophy

Abstract: Cardiomyocyte hypertrophy is the cellular response that mediates pathologic enlargement of the heart. This maladaptation is also characterized by cell behaviors that are typically associated with apoptosis, including cytoskeletal reorganization and disassembly, altered nuclear morphology, and enhanced protein synthesis/ translation. Here, we investigated the requirement of apoptotic caspase pathways in mediating cardiomyocyte hypertrophy. Cardiomyocytes treated with hypertrophy agonists displayed rapid and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 47 publications
5
60
0
1
Order By: Relevance
“…To determine whether caspase 3 is important to this process, we injected the tibialis anterior (TA) muscle with an adenovirus containing a p35-IRES-GFP vector (or GFP alone as a control). The baculovirus p35 protein is a potent biologic inhibitor of caspase 3/7 activity, which we have previously used for in vivo characterization of caspase activity in the heart (19). Infection with the p35-containing virus (Adp35) at 2 d post-cardiotoxin (CTX) injury resulted in a significant reduction in the minimal Feret's diameter (with the majority of fibers measuring between 10-20 μm; 30.03 ± 2.27%) compared with control (AdGFP)-treated muscle (17.33 ± 4.52% of fibers between 10-20 μm) at 14 d postinjury ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether caspase 3 is important to this process, we injected the tibialis anterior (TA) muscle with an adenovirus containing a p35-IRES-GFP vector (or GFP alone as a control). The baculovirus p35 protein is a potent biologic inhibitor of caspase 3/7 activity, which we have previously used for in vivo characterization of caspase activity in the heart (19). Infection with the p35-containing virus (Adp35) at 2 d post-cardiotoxin (CTX) injury resulted in a significant reduction in the minimal Feret's diameter (with the majority of fibers measuring between 10-20 μm; 30.03 ± 2.27%) compared with control (AdGFP)-treated muscle (17.33 ± 4.52% of fibers between 10-20 μm) at 14 d postinjury ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, in prior reports (Putinski et al 16 and Wang et al 17 ), activation of procaspase-3 before procaspase-9 was observed by the parent compound PAC-1. Second, although zinc ion binding sites have been identified on procaspase-9, 36 zymogen procaspase-9 exists as a monomer, and activation by zinc ion chelation requires dimerization.…”
Section: Discussionmentioning
confidence: 96%
“…PAC-1 (chemically, ortho-hydroxy N-acyl hydrazone) is the founding member of this class of compounds, and has shown promise in vitro, 11,13,14 in vivo, 11,15 and as a tool for studying procaspase-3 activation in various systems. 16,17 PAC-1 inhibited growth in primary colon tumors and mouse xenograft models, 11 through zinc ion chelation of executioner procaspase-3 and -7. 12 Recently, a next-generation PAC-1 combinatorial library of 837 compounds was designed and synthesized to identify more potent and cancer cell-selective apoptosis inducers.…”
Section: Introductionmentioning
confidence: 99%
“…As nicely shown by single cell imaging and quantitative systems biology studies of apoptosis, such sub-lethal caspase-3 activity can arise when tipping the balance for expression of proteins relevant in the post-MOMP pathway from pro-apoptotic to anti-apoptotic ones [31,68,69]. Indeed, a recent study also demonstrated that apoptosome dependent, sub-lethal caspase-activity can also lead, and even is essential, in a model of cardiomyocyte hypertrophic remodeling [70]. Specifically using hypertrophy inducing agonists, these study authors demonstrated that caspase-9 and caspase-3 were activated in the cardiomyocytes at an extent that was too low to induce apoptosis.…”
Section: Does Dox-induced Momp Render Functionally Impaired Cardiomyomentioning
confidence: 95%